Efficient Preparation of Bafilomycin A1 from Marine Streptomyces lohii Fermentation Using Three-Phase Extraction and High-Speed Counter-Current Chromatography - Yuan, Ye (Mar Drugs, 2020)
An efficient strategy was developed for the rapid separation and enrichment of bafilomycin A1 (baf A1) from a crude extract of the marine microorganism Streptomyces lohii fermentation. This strategy comprises liquid−liquid extraction (LLE) with a three-phase solvent system (n-hexane–ethyl acetate–acetonitrile–water = 7:3:5:5, v/v/v/v) followed by separation using high-speed counter-current chromatography (HSCCC). The results showed that a 480.2-mg fraction of baf A1-enriched extract in the middle phase of the three-phase solvent system was prepared from 4.9 g of crude extract after two consecutive one-step operations. Over 99% of soybean oil, the main hydrophobic waste in the crude extract, and the majority of hydrophilic impurities were distributed in the upper and lower phase, respectively. HSCCC was used with a two-phase solvent system composed of n-hexane–acetonitrile–water (15:8:12, v/v/v) to isolate and purify baf A1 from the middle phase fraction, which yielded 77.4 mg of baf A1 with > 95% purity within 90 min. The overall recovery of baf A1 in the process was determined to be 95.7%. The use of a three-phase solvent system represents a novel strategy for the simultaneous removal of hydrophobic oil and hydrophilic impurities from a microbial fermentation extract.